Contextual ESP Learning Through Digital Comics in Occupational Safety and Health Education - Ahsanah, Finaty; Istighfaara, Naadiya; Bowo, Eko Ari; Sugiyana, Laely Ufiz; Ardhi, Maharani Nusara (IKIP Siliwangi, 2026)
English for Specific Purposes (ESP) plays a crucial role in preparing Occupational Safety and Health (OSH) students to communicate effectively in professional and industrial contexts. However, ESP instruction in higher education often remains text-based and lacks contextual relevance, resulting in low student engagement and limited comprehension of technical language. This study explores the use of digital comics as a contextual learning medium for ESP instruction in the Occupational Safety and Health (OSH) program. Employing a mixed-method research design, this study involved 40 first-year OSH students at Universitas Muhammadiyah Lamongan. Data were collected through classroom observations, student reflections, semi-structured interviews, and documentation of learning outcomes. The findings indicate that digital comics enhance students’ comprehension of technical vocabulary, improve engagement, and facilitate contextual understanding of workplace communication, such as safety procedures, hazard reporting, and emergency response. Students perceived the digital comics as engaging, relevant, and helpful in bridging theoretical knowledge with real-world occupational scenarios. This study concludes that digital comics are an effective pedagogical medium for contextual ESP learning and recommends their integration into vocational and health-related language instruction.